The results of two-stage optico-functional rehabilitation of patients with refractive disorders and the risk of postoperative asthenopic syndrome after FemtoLASIK - I. A. Mushkova; M. L. Mitronina; T. A. Kornyushina; N. V. Maychuk; L. T. Shamsetdinova (Российский офтальмологический журнал)
Purpose. A comparative analysis of the results of two-stage optico-functional rehabilitation of patients with a high risk of postoperative asthenopic syndrome (AS).Materials and methods. 36 patients (72 eyes) who had no binocular vision at a distance of 5 m and had a symmetrical position of the eyes, or a position close to symmetry, were randomly divided into 2 equal groups of comparison. Patients in both groups underwent functional treatment followed by the correction of refractive errors with FemtoLASIK technology. To eliminate accommodation dysfunctions, a medical device OXYS was used. Diploptic treatment was carried out using a Speckle-M laser apparatus and Bagolini raster glasses. To expand fusional reserves, a prism compensator (OKP-20, Russia) and a Speckle-M laser apparatus were used. The patients of the first group underwent a fast course of medical and functional rehabilitation for 5 working days (2 times a day with a break of 2–3 hours). As an additional pharmacological support, daily instillations of phenylephrine hydrochloride 2.5 % without preservatives were prescribed. The other group received the same functional treatment for 10 working days.Results. After the fast and the standard rehabilitation courses, the patients revealed an increase in absolute accommodation and a decrease in the coefficient of micro fluctuations, an expansion of fusional reserves, an increase in stereovision acuity, and an increased number of cases of binocular vision. No statistically significant difference of clinical and functional parameters obtained as a result of the fast and the standard rehabilitation courses was revealed.Conclusions. Functional and medicament treatment of patients with refractive disorders and the absence of binocular vision prior to FemtoLASIK is shown to be effective. This treatment reduces the risk of postoperative AS and increases the patient’s satisfaction with the results of the surgery.